2014
DOI: 10.3109/14767058.2014.997203
|View full text |Cite
|
Sign up to set email alerts
|

Nasal intermittent positive pressure ventilation with or without very early surfactant therapy for the primary treatment of respiratory distress syndrome

Abstract: NIPPV failure was significantly lower when combined with surfactant treatment, which indicates the critical role of early surfactant treatment in reducing the need for invasive ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Generally, RDS may gradually aggravate in 72 hours with the consumption of replacement surfactant. Therefore, prophylactic, early and enough surfactant replacement therapy can effectively reduce the incidence of intubation and complications in preterm infants with RDS as compared with later selective surfactant administration 27 , which was consistent with the report by Duman N et al 28 The updated meta-analysis showed that, compared with NCPAP group, there was a significant decrease in the need for invasive ventilation in NIPPV group in the preterm infants who received surfactant 19 . In the present study, surfactant administration was enforced in 85.3% (122/143) twin neonates with mean 1.5–1.6 times in early stage, and the overall rates of intubation were similar between the two groups.…”
Section: Discussionsupporting
confidence: 88%
“…Generally, RDS may gradually aggravate in 72 hours with the consumption of replacement surfactant. Therefore, prophylactic, early and enough surfactant replacement therapy can effectively reduce the incidence of intubation and complications in preterm infants with RDS as compared with later selective surfactant administration 27 , which was consistent with the report by Duman N et al 28 The updated meta-analysis showed that, compared with NCPAP group, there was a significant decrease in the need for invasive ventilation in NIPPV group in the preterm infants who received surfactant 19 . In the present study, surfactant administration was enforced in 85.3% (122/143) twin neonates with mean 1.5–1.6 times in early stage, and the overall rates of intubation were similar between the two groups.…”
Section: Discussionsupporting
confidence: 88%
“…22 Adding surfactant instillation to NIPPV treatment resulted in even better outcomes. 29 In our study, we showed that it is possible to deliver significant amounts of surfactant by nebulization during NIV with only minor blood gas changes. The type of ventilator, the CPAP system, and the mode of NIV can have an impact on blood gases and aerosol delivery during nebulization.…”
Section: Discussionmentioning
confidence: 55%
“…There was no statistically significant difference in mortality between the two groups (RR 0.52; 95% CI 0.05 to 5.40). 11 …”
Section: Resultsmentioning
confidence: 99%